The Challenges of Competence-Based Assessment in the Educational Field - Rios-Munoz, D; Herrera-Araya, D (Faculdade de Educacao da Universidade de Sao Paulo, 2017)
The objective of this article is to make a contribution to the discussion and reflection of the formative role of the competence-based assessments in the educational field. Its relationship with the curriculum profiles that is oriented to the new labour context is established. The need to create guidelines, designs, implementations and instrumental developments to determine the impact of learning by competences as a way of evidencing the appropriation of complex integral knowledge is sustained. In order to promote a more participatory and democratic approach to the evaluation system, it is assumed the challenge of competence-based assessments that involve incorporating the main actors of the teaching and learning process. For this purpose a brief description and theoretical-conceptual analysis on the competences in the educational field is carried out. Assessment of competence is pinpointed as a new practice, highlighting the integral and formative criteria of these practices. Additionally, it is analysed how the evaluation by competences can improve learning and pedagogical practices. In conclusion, competence-based assessments are presented as a balance between opportunities and challenges for the educational field, especially those related to the concern in the process prior to the final result of a learning process.